PROJECT-BASED LEARNING (PjBL) UNTUK PAI SELAMA PEMBELAJARAN DARING - ARUM EMA JUWANTI; UNIK HANIFAH SALSABILA; CIKAL JIWANI PUTRI; ALMA LIVIA DEWI NURANY; FITRI NUR CHOLIFAH (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2020)
During the Covid-19 pandemic, the government decided to organize online learning as a diversion for face-to-face learning in schools. For this reason, it is necessary to have technological intervention as a communication medium in learning. There are many learning methods that can be used during online learning, one of which is PjBL. This study aims to determine the benefits of implementing PjBL for Islamic Education subjects during online learning. The data collection method used is literature study through books, journals, and the results of field research conducted by previous researchers that are relevant to this research. The results of the study indicate that in online learning, PjBL is able to increase the creativity of students in carrying out projects and increase the ability of students to use technology as a medium to communicate their work as media to create products.